LITERATUR REVIEW: IDENTIFIKASI PEMANFAATAN LIMBAH KELAPA MUDA SEBAGAI BAHAN PAKAN TERNAK - Andi Zahran Hilmy umar; Yohanes Freadyanus Kasi; maria elisabet Ga'a (Fakultas Pertanian dan Peternakan Universitas Muhammadiyah Bengkulu, 2026)
Young coconut waste is a significant source of organic waste generated from the sale and consumption of young coconuts. Much of this waste—comprising husks, shells, and residual flesh—remains underutilized, posing a potential risk of environmental pollution. Meanwhile, the demand for livestock feed continues to rise alongside the growth of the livestock industry, even as the cost of conventional feed ingredients increases. This study aims to identify types of young coconut waste suitable for use as livestock feed and to examine appropriate processing techniques. The methodology involved a literature review and descriptive analysis of scientific sources regarding the utilization of agricultural waste for animal feed. The findings indicate that young coconut waste—particularly husks and residual flesh—contains organic matter that can serve as a source of fiber and energy for ruminant livestock. Processing methods such as chopping, drying, and fermentation can enhance the nutritional quality and digestibility of these materials. Utilizing young coconut waste as livestock feed offers economic benefits through reduced feed costs and environmental benefits by minimizing organic waste disposal.